2004
DOI: 10.1007/s11102-005-5349-x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Apoplexy During Therapy with Cabergoline in an Adolescent Male with Prolactin-Secreting Macroadenoma

Abstract: Pituitary adenomas are rare in young patients. Prolactinomas are the most common type of pituitary adenomas in children older than 12 years, occurring more often in girls, at a 4.5:1 female-to-male ratio. The clinical presentation may vary according to the age and sex of the patient. Pituitary apoplexy is a rare life-threatening condition caused by a sudden infarction or hemorrhagic necrosis of the pituitary containing an adenoma. A wide variety of conditions can trigger apoplexy such as pituitary irradiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 33 publications
(53 reference statements)
4
34
0
2
Order By: Relevance
“…The main predisposing factors associated to pituitary apoplexy (~25% of cases) are: medication (bromocriptine and cabergoline) [26][27][28] , radiotherapy 29 , pituitary function tests 30,31 , diabetes mellitus, trauma, thrombocytopenia or recent surgery [32][33][34][35][36] . high blood pressure is also considered as a risk factor for pituitary apoplexy although this association is not always seen 1,6 .…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…The main predisposing factors associated to pituitary apoplexy (~25% of cases) are: medication (bromocriptine and cabergoline) [26][27][28] , radiotherapy 29 , pituitary function tests 30,31 , diabetes mellitus, trauma, thrombocytopenia or recent surgery [32][33][34][35][36] . high blood pressure is also considered as a risk factor for pituitary apoplexy although this association is not always seen 1,6 .…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…The patient needed dopamine support to maintain her vital signs during LDLT and re-laparotomy. Knoepfelmacher et al reported that a causal relationship between dopamine agonist (bromocriptine) and apoplexy has been suggested because adenomas have sometimes shown necrosis at surgery after bromocriptine treatment [11,12]. This patient received the dopamine agonist only because of the surgery, so this factor might be associated with this complication.…”
Section: Discussionmentioning
confidence: 97%
“…Several suggested risk factors that predispose a tumor to apoplexy include tumor size, nonfunctioning or prolactin-producing subtypes, invasion of the The level of compression was above the left posterior communicating artery, as seen on lateral left common angiography (c, black arrow). Postoperative MRI shows extensive resection of the prolactinoma with some residual tumor along the left cavernous sinus (d) cavernous sinus, and coagulopathy [5][6][7][8][9][10][11]. Though no rate is reported, pituitary apoplexy is rare in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%